Promising approaches for simultaneous enhancement of medicinally significant benzylisoquinoline alkaloids in opium poppy - Aghaali, Zahra; Naghavi, Mohammad Reza; Zargar, Meisam (Frontiers in Plant Science, 2024)
Benzylisoquinoline alkaloids (BIAs) produced in opium poppy have been evidenced to heal patients suffering from various diseases. They, therefore, hold an integral position in the herbal drug industry. Despite the adoption of several approaches for the large-scale production of BIAs, opium poppy remains the only platform in this purpose. The only disadvantage associated with producing BIAs in the plant is their small quantity. Thus, recruiting strategies that boost their levels feels necessary. All the methods which have been employed so far are just able to enhance a maximum of two BIAs. Thus, if these methods are utilized, a sizable amount of time and budget must be spent on the synthesis of all BIAs Hence, the exploitation of strategies which increase the content of all BIAs at the same time is more commercially effective and time-saving, avoiding the laborious step of resolving the biosynthetic pathway of each compound. Exposure to biotic and abiotic elicitors, development of a synthetic auto-tetraploid, overexpression of a WRKY transcription factor, formation of an artificial metabolon, and suppression of a gene in the shikimate pathway and a miRNA are strategies that turn opium poppy into a versatile bioreactor for the concurrent and massive production of BIAs. The last three strategies have never been applied for BIA biosynthetic pathways.